Contribution of Phosphorylation Modification to Stability and Antibacterial Activity of Egg White Protein Nanogels Loaded with Cinnamon Bark Essential Oil - Sheng-Qi Rao; Xin-Ru Gao; Hui Liu; Zhi-Rong Wang; Zhen-Quan Yang (Gels, 2024)
This study evaluated the potential usage of phosphorylated egg white protein (P-EWP) nanogels fabricated via microwave-induced phosphorylation modification and gel process and further ultrasonic nanometrization as novel delivery systems for cinnamon bark essential oil (CBEO). Compared to EWP-CBEO nanogels without chemical phosphorylation, the obtained P-EWP-CBEO nanogels have shown smaller average hydrodynamic diameter (133.6 nm), relatively uniform size distribution (polydispersity index around 0.265), enhanced negative surface charge (−35.4 mV), and improved stability under the conditions of high temperature (up to 90 °C) and ionic strength (up to 200 mM NaCl). Moreover, P-EWP-CBEO nanogels, with hydrophobic interactions and disulfide bonds as the main intermolecular forces, exhibited a remarkable conformational change in microstructures. In addition, the results of the antibacterial experiments on Escherichia coli, Staphylococcus aureus, and Listeria monocytogenes showed that the MIC values of P-EWP-CBEO nanogels were two times lower than those of EWP-CBEO nanogels and could completely inhibit the growth of pathogenic bacteria within 108 h. Hence, we have suggested that P-EWP-CBEO nanogels are successfully fabricated with improved physicochemical properties as novel potential natural preservatives in the food industry.